310 A COMPARATIVE ANALYSIS OF THE IRISH POST-GRADUATE GERIATRIC TRAINING SCHEME WITH THE EUROPEAN POST-GRADUATE CURRICULUM IN GERIATRIC MEDICINE. (25th October 2022) - Murphy, R; McCarthy, C; Reddin, C; Canavan, M; O'Dwyer, C; Mulroy, M; O'Donnell, M
Abstract: Background: Minimum training recommendations to become a specialist geriatrician in the EU have been published. In this study we sought to evaluate the curriculum of the higher specialist training scheme in Geriatric Medicine in Ireland and examine how it compares with the knowledge recommendations from the European post-graduate curriculum in Geriatric medicine, which is endorsed by both the European Geriatric Medicine Society (EuGMS) and the European Academy of Medicine of Ageing (EAMA). Methods: In this study we examined the content of didactic study-day lectures given over a five-year rolling period which is the minimum duration of the higher specialist training programme in Geriatric medicine in Ireland. We also examined the published Irish curriculum and compared how both the Irish curriculum and content of the study-days matches up with the 36 items that are identified as the core knowledge content in the European post-graduate curriculum. Results: There were 24 study days delivered over a five-year time period. The Irish geriatric medicine curriculum formally outlined that 30 of the 36 knowledge areas proposed in the European curriculum should be formally covered during post-graduate geriatric training in Ireland. The European curriculum recommended formal teaching in sarcopenia, sleep disorders, tissue viability, iatrogenic care delivered disorders, sexuality in older adults and geron-technology/e-health, none of which were referred to in the Irish curriculum. However, despite this discrepancy, formal teaching was delivered on 92% (n = 33) of proposed areas. Pain assessment, sleep disorders and tissue viability were areas not covered in Irish didactic study-days. 24 of 36 topics were covered at least twice. Conclusion: There was high concordance between the content of the Irish and European post-graduate curriculum in Geriatric medicine. Benchmarking against European training standards is an opportunity to ensure that parity of education and training is achieved across the EU.